Impact assessment of Sea Level Rise (SLR) on coastal erosion through multiple-criteria index in Pantai Remis, Perak - Nurul Ain Liyana Hamzah; Khairul Nizam Abdul Maulud; Noorashikin Md Noor; Wan Hanna Melini Wan Mohtar; Fazly Amri Mohd; Nor Aizam Adnan; Syed Ahmad Fadhli Syed Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Extreme climate changes have led to natural disasters, especially sea level rise, which leads to coastal erosion and can affect the safety and economy of the local community. Through an index of different criteria, this study aims to find out how sea level rise affects erosion along the coast in Pantai Remis, Perak. A spatial model for determining the impact of sea level rise on coastal erosion was designed, as was a risk assessment framework for the impact of sea level rise on coastal erosion using the multi-criteria index method. This study focuses on the geomorphology, coastal slope, coastal elevation, coastal buffers, tidal range, wind speed, building density, population activity, and road network. As a result of the calculation of indices and weights for the study, four out of 28 (14.3%) management units are in areas that received a very high impact of sea level rise on coastal erosion. Areas classified as very high are likely to be affected by the movement of small boats and cause the level of erosion in the area to worsen. Three out of 28 (10.7%) management units are classified as high, 13 (46.4%) are classified as moderate, and eight out of 28 (28.6%) management units are low. Overall, Pantai Remis, Perak, is a beach with a moderate impact of coastal erosion due to sea level rise. This approach allows for the incorporation of multiple factors and the prioritization of mitigation measures based on their relative importance, which can be useful for decision-making and resource allocation.